Exercise recovery practices of wheelchair court sports athletes - Murphy, C. J.; Mason, B. S.; Goosey-Tolfrey, V. L. (The Journal of Strength and Conditioning Research, 2021)
Research that describes the recovery practices of Para-athletes around training and competition is limited. This study investigated if and why athletes in wheelchair court sports (basketball, rugby, and tennis) use recovery strategies, what type of strategies are used, and whether the period of the season influences the prevalence of use. A cross-sectional questionnaire was developed to acquire data pertaining to individual characteristics, recovery habits, reasons for use/nonuse, the use of specific recovery strategies, and lifestyle habits. One hundred forty-four athletes (92 = international and 52 = national/club) completed the questionnaire online. In total, 85% (n = 122) of athletes reported using at least one type of recovery strategy, yet most specific types of recovery strategies were not popular (<34% of recovery strategy users). The most commonly used type of recovery strategy was stretching (n = 117), whereas both stretching and heat-related recovery were the most highly rated types of recovery strategies (µ = 4.2/5). The 3 most prevalent reasons for use across all strategies were "reduces muscle soreness," "reduces muscle tightness," and "reduces muscle spasms." The prevalence of sleep complaints was apparent with 38% (n = 55) of respondents reporting difficulties sleeping. This study highlights that although the frequent use of well-known recovery practices is positive, the lack of diversity in strategies implemented may have implications due to the specific requirements of exercise recovery. Therefore, strength and conditioning professionals should educate wheelchair athletes further around this area and increase the range of recovery-specific and impairment-specific strategies used.